2022
DOI: 10.1007/s10157-022-02188-y
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with SARS-CoV-2 antibody titers and prognosis of breakthrough infection in hemodialysis patients

Abstract: Background The mortality rate of Coronavirus disease 2019 (COVID-19) is extremely high in hemodialysis patients (HDP). These patients also develop lower antibody titers after vaccination. Therefore, factors associated with antibody titers and vaccine efficacy in HDP with breakthrough infection need to be investigated. Methods We measured anti-S1 antibody titers in HDP (n = 104) and controls (n = 35), evaluating the influence of background on HDP by multivariable regression analysis. We classified 26 HDP patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…It is now known that these antibodies only represent a component of the immune response, and that the direct role of memory T cells in killing virus-infected cells is equally fundamental [ 7 ]. Nevertheless, the presence of neutralizing antibodies against SARS-CoV-2 is still an important indicator used to determine whether a subject might have a positive response to the vaccine, and their presence is also evaluated in some studies aimed at exploring possible associations with COVID-19 symptoms and prognosis [ 1 , 2 , 3 , 4 , 5 , 6 , 8 , 9 ]. The main target of the anti-SARS-CoV-2 neutralizing antibodies investigated after the performance of the vaccination is the spike (S) protein, and in particular its Receptor-binding Domain (RBD) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that these antibodies only represent a component of the immune response, and that the direct role of memory T cells in killing virus-infected cells is equally fundamental [ 7 ]. Nevertheless, the presence of neutralizing antibodies against SARS-CoV-2 is still an important indicator used to determine whether a subject might have a positive response to the vaccine, and their presence is also evaluated in some studies aimed at exploring possible associations with COVID-19 symptoms and prognosis [ 1 , 2 , 3 , 4 , 5 , 6 , 8 , 9 ]. The main target of the anti-SARS-CoV-2 neutralizing antibodies investigated after the performance of the vaccination is the spike (S) protein, and in particular its Receptor-binding Domain (RBD) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies regarding the association of such vaccination with severe COVID-19 progression in dialysis patients are limited. Toda et al reported that full vaccination status was associated with reduced disease severity, including severe COVID-19, in dialysis patients, though the number of cases investigated was small ( n = 26) and the association was not adjusted using known risk factors [ 11 ]. In another study, Ashby et al noted that full vaccination status reduced the need for intubation, shown to correspond to severe COVID-19, in dialysis patients after adjustment for known risk factors including age and diabetes, though the difference was not significant [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination began sequentially in February 2021 for healthcare workers, then in June 2021 for individuals with underlying medical conditions, including dialysis patients, with public and private sectors working together to promote vaccination. Although the immune response to such vaccine treatment has been reported to be compromised in dialysis patients [ 9 , 10 , 11 ], vaccination has also been shown to reduce the rate of non-severe COVID-19 cases as well as COVID-19-related mortality in patients receiving that treatment [ 12 , 13 , 14 , 15 , 16 , 17 ]. However, few studies have assessed a dialysis patient cohort regarding the relationship of vaccination with the progression to severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Our search strategy identified a total of 6 studies 8 , 9 , 10 , 11 , 12 , 13 . involving 6244 adult patients with COVID-19, including 3744 in the unvaccinated group and 1921 in the two-dose vaccination group, were included in this meta-analysis.…”
Section: Dear Editormentioning
confidence: 99%